Evidence for the Presence of Bacteria-specific Proteins in Sterile Crown Gall Tumor Tissue - Chadha, Kailash C. (1971)
Cross-reacting antigens were found in bacteria-free crown gall tumor tissue tested with serum prepared against Agrobacterium tumefaciens (Smith and Towns.) Conn., but no such antigens were detected in callus tissue. Soluble proteins from tumor tissue, callus tissue, and the crown gall bacteria were fractionated on a DEAE-Sephadex (A-50) column. The diethylaminoethyl-Sephadex elution profile for tumor tissue showed three protein fractions that were not detected in the callus tissue. Two of these protein fractions were shown to be exclusively bacteria specific. Besides these qualitative differences between the two tissues, significant quantitative differences in the amount of protein fractions were also observed. The diethylaminoethyl-Sephadex column fractions from tumorigenic strain of A. tumefaciens corresponding in position to the three additional peaks in the tumor tissue also showed cross-reacting antigens when tested with serum prepared against sterile tumor tissue. It is suggested that tumor formation by A. tumefaciens involves integration of the bacterial genome into the host-cell genome.